Economic Order Model With Quadratic Backorder Costs (International Journal of Scientific Research and Management (IJSRM), 2014)
The paper considers backorder costs as a quadratic cost depending on the length of time of the backorder. The quantity ordered is Q and the reorder level is R. We assume that the backorder cost Cβ(t) is b1 + b2t + b3t 2 . Where b1, b2 and b3 are the coefficients with respect to t, t1 e and t2 , The equations for the linear cost is derived first in section 1 by deriving the expected backorder cost per cycle using the assumption that demand follows the normal distribution. We extend the method of analysis to derive the backorder costs when the backorder costs is a quadratic function of the length of time of a backorder. The additional costs to the incurred by the linear costs to the costs that is not time dependent is.ECONOMIC ORDER MODEL WITH QUADRATIC BACKORDER COSTS.